The Time Course for Processing Vowels and Lexical Tones: Reading Aloud Thai Words. (June 2016) - Davis, Chris; Schoknecht, Colin; Kim, Jeesun; Burnham, Denis
Three naming aloud experiments and a lexical decision (LD) experiment used masked priming to index the processing of written Thai vowels and tones. Thai allows for manipulation of the mapping between orthography and phonology not possible in other orthographies, for example, the use of consonants, vowels and tone markers in both horizontal and vertical orthographic positions (HOPs and VOPs). Experiment 1 showed that changing a vowel between prime and target slowed down target naming but changing a tone mark did not. Experiment 1 used an across item-design and a different number of HOPs in the way vowels and tones were specified. Experiment 2 used a within-item design and tested vowel and tone changes for both 2-HOP and 3-HOP targets separately. The 3-HOP words showed the same tone and vowel change effect as Experiment 1, whereas 2-HOP items did not. It was speculated that the 2-HOP result was due to the variable position of the vowel affecting priming. Experiment 3 employed a more stringent control over the 2-HOP vowel and tone items and found priming for the tone changes but not for vowel changes. The final experiment retested the items from Experiment 3 with the LD task and found no priming for the tone change items, indicating that the tone effect in Experiment 3 was due to processes involved in naming aloud. In all, the results supported the view that for naming a word, the development of tone information is slower than vowel information.